Can Emerging Countries Become Leaders in the Global Context? - Abdul Holik (Owner : Riset dan Jurnal Akuntansi, 2018)
Economic growth of emerging countries was convinced has made many changes in global economic architecture. In the post-world war 2, United States of America and several western European countries stand as great power. Today their role allegedly start to be replaced by emergence of new giants such as China, India, and some other emerging markets. Indonesia according to analysts and reports of global economic outlook will include those new giants in year 2050. This belief is not a mistake. Nevertheless, those thoughts need more consideration and must be balanced with facts and whole study regarding economic performance and the quality of government. We conclude that analysis and reports are overestimated. This study discusses any possibilities that can occur regardless those analysis and report. But we still believe that emerging countries actually can become new leaders in global context in conditional on their capability to resolve any problems which very urgent in current situation.